A localised clustering scheme to detect attacks in wireless sensor network. (2015) - Joby, P.P.; Sengottuvelan, P.
Wireless sensor networks (WSN) is an embryonic communication technique in the universe to be engaged for precarious circumstances resembling battle arenas and viable applications such as construction, transportation surveillance, territory monitoring, clever homes etc. Currently, a wireless sensor network facing a foremost problem is the result from security issues. There are many security methodologies available for a wireless sensor network. Generally classified as two levels; one is low level, further categorised into privacy, key establishment, trusted network, secrecy, authentication, secure routing etc. The second one is high level, further categorised into secure group management, intrusion detection, data integrity etc. This research focusing on the network availability, prior revisions offered to protect the network beside denial of service attacks with the use of traffic monitoring proxies on some nodes. But if the governor nodes are miserable, then it is vulnerable to the network. To overcome this, the research puts forth a mechanism called election method to elect the control nodes in a cluster. To simulate this methodology, packet tracer tool is used.